Empowering Marginalized Groups: Unveiling the Benefits of Community Integration in Public Services Decision-Making - Jonathan Jacob Paul Latupeirissa; I Wayan Tu Adi; Evelyn B. Valencia (Journal of Governance and Public Policy, 2025)
This research highlights the critical relationship between public participation in decision-making and the enhanced efficiency of public service delivery, particularly for marginalized communities. Through a systematic review of international literature sourced from the Scopus database, the study examines how inclusive governance practices strengthen the engagement of underrepresented groups within government institutions. The findings emphasize the vital role of stakeholder participation in shaping effective, responsive, and inclusive public policies. The analysis reveals that inclusive decision-making not only improves the quality and accessibility of public services but also promotes more equitable and accountable governance. This research contributes to the broader discourse on participatory governance by offering a comprehensive analysis of community engagement dynamics and demonstrating how targeted interventions can help address structural inequalities in public administration. The novelty of this study lies in its emphasis on the transformative potential of inclusive policymaking, particularly in amplifying the voices and lived experiences of marginalized groups. By integrating these perspectives into policy development, governments can more effectively meet the diverse needs of their populations. Moving forward, the study advocates for identifying and implementing strategic mechanisms to increase the participation of marginalized communities in institutional decision-making, thereby advancing a more just and equitable society.